New bimaxillary orthognathic surgery planning and model surgery based on the concept of six degrees of freedom - Jeon, Jaeho; Kim, Yongdeok; Kim, Jongryoul; Kang, Heejea; Ji, Hyunjin; Son, Woosung (Korean journal of orthodontics (2012), 2013)
The aim of this paper was to propose a new method of bimaxillary orthognathic surgery planning and model surgery based on the concept of 6 degrees of freedom (DOF). A 22-year-old man with Class III malocclusion was referred to our clinic with complaints of facial deformity and chewing difficulty. To correct a prognathic mandible, facial asymmetry, flat occlusal plane angle, labioversion of the maxillary central incisors, and concavity of the facial profile, bimaxillary orthognathic surgery was planned. After preoperative orthodontic treatment, surgical planning based on the concept of 6 DOF was performed on a surgical treatment objective drawing, and a Jeon's model surgery chart (JMSC) was prepared. Model surgery was performed with Jeon's orthognathic surgery simulator (JOSS) using the JMSC, and an interim wafer was fabricated. Le Fort I osteotomy, bilateral sagittal split ramus osteotomy, and malar augmentation were performed. The patient received lateral cephalometric and posteroanterior cephalometric analysis in postretention for 1 year. The follow-up results were determined to be satisfactory, and skeletal relapse did not occur after 1.5 years of surgery. When maxillary and mandibular models are considered as rigid bodies, and their state of motion is described in a quantitative manner based on 6 DOF, sharing of exact information on locational movement in 3-dimensional space is possible. The use of JMSC and JOSS will actualize accurate communication and performance of model surgery among clinicians based on objective measurements.